03 Debate: a minority of lupus patients (will) need a biologic!. (1st September 2020) - Urowitz, Murray
Abstract : Obviously, the expected role for biologic therapy in lupus is to control disease activity and prevent damage and co-morbidities, but what is the evidence that we are not faring well in those areas? Over the past 5 decades there has been a dramatic improvement in survival rates for patients with systemic lupus erythematosus (SLE) perhaps due to a combination of earlier diagnosis, more effective treatments, recognition of important comorbidities and their earlier diagnosis and treatment. Currently, the 20-year survival rate is 80%! 1 2 Standardised Mortality Ratios have decreased from over 14 in the 1970s to just over two in the 2000s. 3 Furthermore, the cause of the 206 deaths in our cohort due to lupus was only 19% whereas deaths from atherosclerotic disease was 21.5% and from infection 34.6% neither of which would require a biologic. 4 In terms of disease activity, in the first decade of disease the adjusted mean Systemic Lupus Erythematosus Disease Activity Index-2K (AMS) has decreased from 7.94 in the 1970s to 5.16 in the 2000s and the percentage of time on prednisone >7.5 mg was significantly lower, all indicating much improved control of disease. This is corroborated by the fact that patients are spending a significant portion of their disease over the first 10 years in clinical remission. So, if patients are surviving longer with less active disease and lower steroid therapy, are they suffering more co-morbidities? The prevalence of atherosclerotic vascular events has similarly declined over the past 4 decades in our cohort from a prevalence from 11.0% to 3.8% (an incidence of 0.44 per 100 patient years) an incidence seen also in the SLICC cohort. 5 This dramatic decrease is due to better control of lupus disease activity and also treatment of atherosclerotic risk factors. Finally, when one looks at the randomised controlled trials with biologics in lupus, more than a third of the placebo-treated patients who were getting standard of care achieved their respective primary endpoints. The difference in outcome in those getting biologics was only in the range 10% greater, hardly a major impact. In summary, lupus is being much better controlled, less steroid is being used, co-morbidities are less and biologics to date have had a minimal impact. A Minority of Lupus Patients Will Need a Biologic! Learning Objectives: Describe how lupus survival has improved dramatically in past 5 decades Explain how mortality in lupus is now less related to lupus and more related to co-morbidities or infection Demonstrate that lupus patients are currently spending more of their time in remission and on less corticosteroids Show that the major co-morbidity atherosclerotic vascular disease has decreased dramatically References: Pons-Estel GJ, Alarcon GS, Scofield L, et al . Understanding the epidemiology and progression of systemic lupus erythematosus. Semin Arthritis Rheum 2010;39(4) :257–68. Urowitz MB, Bookman AA, Koehler BE, et al . The bimodal mortality pattern of systemic lupus erythematosus. Am J Med 1976;60(2) :221–5. Bernatsky S, Boivin JF, Joseph L, et al . Mortality in systemic lupus erythematosus. Arthritis Rheum 2006;54(8) :2550–7. Urowitz MB, Su J, Gladman DD. Atherosclerotic Vascular Events in Systemic Lupus Erythematosus: An Evolving Story. J Rheumatol 2019:jrheum.180986. Urowitz MB, Gladman DD, Anderson NM, et al . Cardiovascular events prior to or early after diagnosis of systemic lupus erythematosus in the systemic lupus international collaborating clinics cohort. Lupus Sci Med 2016;3(1) :e000143.